History on Television. - Gray, Ann (Taylor and Francis, 2012)
In recent years non-fiction history programmes have flourished on television. This interdisciplinary study of history programming identifies and examines different genres employed by producers and tracks their commissioning, production, marketing and distribution histories. With comparative references to other European nations and North America, the authors focus on British history programming over the last two decades and analyse the relationship between the academy and media professionals. They outline and discuss often-competing discourses about how to 'do' history and the underly.